Kevin A. Morrison (ed.), The Companion to Victorian Popular Fiction. Jefferson, NC: McFarland, 2018, 312 pp. US $45 (paperback) ISBN 9781476669038. Issue 1 (2019) - Russell, Anne-Louise
No abstract available